Physico-Chemical Parameters Of Complex Formation Of The Molybdenum Ion - Assistant Ubaydullaeva Saidakhon; Assistant Jurayev Adulaziz Ilxomjon ugli (Global Scientific Publishing, 2023)
The study of the effect of molibdenium on dimethylglioxim from the composition of adsorbents used in this article, found that the optimum conditions in the bun were calculated and determined graphically by means of a spectrophotometer. The analysis was determined on the CFC-2
Keywords: Mo (III) ions; bentonite; used MDEA solution